Taguchi-based design of experiments to optimize the parameters of Hydrogen-Hydrogen-Oxygen based welding - Desi Fajarwati; Deni Shidqi Khaerudini (SINERGI, 2022)
This study discusses the design of a hydrogen-hydrogen-oxygen (HHO) based welding tool, which uses the concept of water electrolysis through a dry cell generator. To determine the optimal design of the HHO dry cell generator, a design experiment was carried out using the Taguchi method by taking into account several parameters, namely the configuration of the electrode plate, the duty cycle Pulse Width Modulation (PWM), the type of catalyst, the electrolyte concentration, and the thickness of the gasket of the electrode plate. Each parameter is varied in 4 levels so that 16 kinds of experiments are obtained with an orthogonal array. In addition, the Combustion temperature data was collected after determining the optimal design. The experimental results show that this HHO-based welding tool is able to produce an average temperature reach of 1063.85 °C.